Challenges and Solutions in B3 Waste Management at RSUD X: An Analysis Based on Ministerial Regulations - Permana, Eko Adittya; Hardiana, Hedy (Utan Kayu Publishing, 2024)
Hospital services provide significant benefits to the community and generate hazardous and toxic waste (B3) that poses high risks if not properly managed. B3 waste management in hospitals must comply with government regulations, such as Minister of Health Regulation No. 02 of 2023 and Minister of Health Regulation No. 07 of 2019. This study aims to analyze the effectiveness of B3 waste management policies at Hospital X and identify the factors affecting their implementation. The research employs a Realist Evaluation methodology using qualitative methods. Seventeen informants, selected through purposive sampling, including management heads, quality committee members, department heads, and field technical officers, were interviewed in-depth. The findings indicate challenges in implementing B3 waste management policies, such as a lack of trained personnel, inadequate infrastructure, and limited budget. While the policies based on Minister of Health Regulation No. 02 of 2023 and Minister of Health Regulation No. 07 of 2019 have been successfully implemented, there are still challenges that need to be addressed to achieve the desired targets. This study provides significant contributions to the development of more effective B3 waste management policies in the future. Abstrak: Kegiatan pelayanan di rumah sakit tidak hanya memberikan manfaat besar bagi masyarakat, namun juga menghasilkan limbah B3 yang berisiko tinggi jika tidak dikelola dengan baik. Pengelolaan limbah B3 di rumah sakit perlu mengikuti kebijakan pemerintah, seperti Permenkes Nomor 02 Tahun 2023 dan Permenkes Nomor 07 Tahun 2019. Penelitian ini bertujuan untuk menganalisis efektivitas kebijakan pengelolaan limbah B3 di Rumah Sakit X dan mengidentifikasi faktor-faktor yang mempengaruhi pelaksanaannya. Penelitian menggunakan metodologi Realist Evaluation dengan metode kualitatif. Sebanyak 17 informan yang dipilih secara purposive sampling, termasuk kepala manajemen, komite mutu, kepala ruangan, dan petugas teknis lapangan, diwawancarai mendalam. Hasil penelitian menunjukkan kendala dalam implementasi kebijakan pengelolaan limbah B3, termasuk kekurangan SDM yang terlatih, infrastruktur yang tidak memadai, dan anggaran yang terbatas. Kebijakan pengelolaan limbah B3 berdasarkan Permenkes No. 02 Tahun 2023 dan Permenkes No. 07 Tahun 2019 telah berhasil diimplementasikan, namun masih terdapat tantangan yang perlu diatasi untuk mencapai target yang diharapkan. Penelitian ini memberikan kontribusi penting bagi pengembangan kebijakan pengelolaan limbah B3 yang lebih efektif di masa mendatang.